2023
DOI: 10.31098/jess.v1i2.1578
|View full text |Cite
|
Sign up to set email alerts
|

Absenteeism of Some Students in Secondary School in Sokoto East, Nigeria

Yusuf Yahaya Miya,
Yusuf Sarkingobir,
Abbas Abubakar Hiliya
et al.

Abstract: Education is a right to every child, but Sokoto is suffering from many issues ravaging education, therewith, children/ adult abandoning school/ class is one of the sufferings of education in the area. The objective of this study is to evaluate the school/ class absenteeism in school in Sokoto East, Nigeria. The demographic characteristics of respondents shows that; all the respondents are Muslims, Hausa/ Fulani, and males (100.0%). The education was degree (33.7%), Students (50.0%), and lastly higher national … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Coping with conflicts, some students resort to absenteeism, impacting their academic advancement. Furthermore, to escape the school environment and the associated conflicts, some students engage in alternative activities, such as farming [18]. A student expressed.…”
Section: "Many Of Us Choose To Comply With Directives From School Pri...mentioning
confidence: 99%
See 2 more Smart Citations
“…Coping with conflicts, some students resort to absenteeism, impacting their academic advancement. Furthermore, to escape the school environment and the associated conflicts, some students engage in alternative activities, such as farming [18]. A student expressed.…”
Section: "Many Of Us Choose To Comply With Directives From School Pri...mentioning
confidence: 99%
“…Absenteeism, truancy, and transfers: Findings show that Conflicts manifest in absenteeism among both teachers and students, showcasing a preference for avoiding the individuals involved rather than confronting misunderstandings. It was revealed that Teachers avoid coming to work, and students choose to be absent to escape uncomfortable situations [18]. Additionally, conflicts lead to unplanned transfers of both teachers and students.…”
Section: Poor Academic Performancementioning
confidence: 99%
See 1 more Smart Citation